2018
DOI: 10.1002/jgm.3060
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing atrial‐specific gene expression using a calsequestrin cis‐regulatory module 4 with a sarcolipin promoter

Abstract: Background Cardiac gene therapy using the adeno‐associated virus serotype 9 vector is widely used because of its efficient transduction. However, the promoters used to drive expression often cause off‐target localization. To overcome this, studies have applied cardiac‐specific promoters, although expression is debilitated compared to that of ubiquitous promoters. To address these issues in the context of atrial‐specific gene expression, an enhancer calsequestrin cis‐ reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…A plasmid encoding HA-tagged ubiquitin was a gift of Dr. Edward Yeh (Addgene #18712) 80 . A plasmid containing the sarcolipin promotor driving luciferase (pTR.SLN.Luc) was a gift of Dr. Dongtak Jeong 81 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A plasmid encoding HA-tagged ubiquitin was a gift of Dr. Edward Yeh (Addgene #18712) 80 . A plasmid containing the sarcolipin promotor driving luciferase (pTR.SLN.Luc) was a gift of Dr. Dongtak Jeong 81 .…”
Section: Methodsmentioning
confidence: 99%
“…A pTR-SLN-Luc plasmid, containing 1029 nt from the human SLN promoter upstream of firefly luciferase, was a gift of Dr. Dongtak Jeong 81 . The pRL-SV40P plasmid, containing the SV40 promoter driving Renilla luciferase, was a control and was a gift of Ron Prywes (Addgene plasmid #27163) 88 .…”
Section: Methodsmentioning
confidence: 99%
“…Generation of AAV expressing CCN5, AAV9‐CCN5, was described in our previous work 7 . AAV9‐VLP (Virus‐like particle), viral particles that contain no viral genome, 17 was used as a control virus throughout this study.…”
Section: Methodsmentioning
confidence: 99%
“…The luciferase reporter system of ROR γ was conducted as follows. The promoter sequence of ROR γ was obtained for GeneCopoeia (Rockville, MD, USA), a web portal for promoter region clones (http://www.genecopoeia.com) [24]. The detailed ROR γ promoter sequence in this study contains the core promoter sequence of ROR γ , which was reported previously [8].…”
Section: Methodsmentioning
confidence: 99%